The Conscript: A Story of the French war of 1813 - Erckmann-Chatrian (Salt Lake City, UT : Project Gutenberg, 2010)
"The Conscript: A Story of the French War of 1813" by Erckmann-Chatrian is a historical novel written in the late 19th century. The book explores the gravity of conscription during the Napoleonic wars, particularly focusing on the life of the protagonist, Joseph Bertha, who is torn away from a peaceful existence and his betrothed by the call to arms. It delves into the emotional and moral complexities of war, highlighting the personal struggles of individuals caught in the larger machinery of military glory. At the start of the story, Joseph Bertha, an apprentice watchmaker in Phalsbourg, reflects on the grandeur and allure of Napoleon's military prowess, which resonates throughout his village. As he eagerly anticipates his upcoming visits to his beloved, Catharine, he wrestles with the fear of being conscripted into service due to his lameness. This dread intensifies with the ongoing news of soldiers departing for war and the harsh conditions faced by those who return. The opening chapters vividly depict the community's mix of excitement and terror surrounding military conscription, and Joseph's internal conflict as the political and social pressures of the era encroach upon his simple, hopeful life. (This is an automatically generated summary.)
Sequel: Waterloo, #31289.
Release date is 2010-02-15
Produced by Al Haines
Keywords: Napoleon I, Emperor of the French, 1769-1821 -- Fiction; Napoleonic Wars, 1800-1815 -- Fiction; Wars of Liberation, 1813-1814 -- Fiction